2014
DOI: 10.1071/py12117
|View full text |Cite
|
Sign up to set email alerts
|

Identifying culturally appropriate strategies for coronary heart disease secondary prevention in a regional Aboriginal Medical Service

Abstract: Aboriginal Australians experience high rates of coronary heart disease (CHD) at an early age, highlighting the importance of effective secondary prevention. This study employed a two-stage process to evaluate CHD management in a regional Aboriginal Medical Service. Stage 1 involved an audit of 94 medical records of clients with documented CHD using the Audit and Best Practice in Chronic Disease approach to health service quality improvement. Results from the audit informed themes for focus group discussions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(50 citation statements)
references
References 19 publications
0
49
0
Order By: Relevance
“…The results from the methodological quality assessment are provided in Supplementary file 3. One was rated high quality, 28 seven were rated good quality, 27,29,34 and one, reported in two articles, was rated moderate quality 25,26 . A lack of clarity about how researchers' values and prior knowledge influenced studies was the main methodological concern potentially undermining the credibility of the findings that informed our syntheses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results from the methodological quality assessment are provided in Supplementary file 3. One was rated high quality, 28 seven were rated good quality, 27,29,34 and one, reported in two articles, was rated moderate quality 25,26 . A lack of clarity about how researchers' values and prior knowledge influenced studies was the main methodological concern potentially undermining the credibility of the findings that informed our syntheses.…”
Section: Resultsmentioning
confidence: 99%
“…All the studies were published between 2004 and 2014. Six used mixed methods 25–27,30,31,33,34 . Four used focus groups and interviews, 27,31–33 four used only interviews, 25,26,28,30 and one used only focus groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…159 Other studies used mixed methods to explore social phenomena likely to be priorities for Aboriginal and Torres Strait Islander peoples including smoking cessation, 154 teenage pregnancy, 161 and cardiovascular chronic disease management in primary care. 157 One study, described in Chapter 2, used qualitative methods to explore Aboriginal and Torres Strait Islander peoples' priorities, and then used quantitative methods to respond to these priorities. 241 Consistent with the transformative paradigm, Burgess found Aboriginal people living in a remote community had better health outcomes when they participated in activities consistent with "caring for country".…”
Section: Mixed Methods Research Involving Aboriginal and Torres Straimentioning
confidence: 99%
“…4 Despite these limitations, a brief or rapid review involving one relevant database over a recent five year period provides useful information on the quantity of research produced in a given setting which was the aim of the review by Eades et al 4 Moreover, one evaluation of four rapid reviews found that their findings, while not as extensive, did not differ greatly from four completed systematic reviews on the same topics. 101 Cross-sectional design Yes a Gardner et al 2015 102 Cross-sectional design No Lalla et al 2015 103 Cross-sectional design Yes Radford et al 2015 104 Cross-sectional design Yes Hopkins et al 2015 105 Cross-sectional design No Arjunan et al 2015 106 Cross-sectional design No Katzenellenbogen et al 2015 107 Cross-sectional design No Pearce et al 2015 108 Cross-sectional design No Spurling et al 2014 109 Cross-sectional design Yes a Scott et al 2014 110 Cross-sectional design No Timms et al 2014 111 Cross-sectional design No Chung et al 2014 112 Cross-sectional design Yes Askew et al 2013 113 Cross-sectional design Yes a Lopez et al 2014 114 Cross 141 Qualitative Yes 153 Mixed methods Yes Gould et al 2015 154 Mixed methods No Jersky et al 2015 155 Mixed methods No Dennis et al 2015 156 Mixed methods No Govil et al 2014 157 Mixed methods Yes Thomas et al 2013 158 Mixed methods No Canuto et al 2013 159 Mixed methods No Homer et al 2012 160 Mixed methods No Larkins et al 2011 161 Mixed methods No Harris et al 2014 162 Cohort study No McDonald et al 2014 163 Cohort study No Jamieson et al 2013 164 Cohort study No Knight et al 2013 165 Cohort study No Webster et al 2013 166 Cohort study No Davis et al 2012 167 Cohort study No Robinson et al 2012 …”
Section: Sparse Research In Urban Populationsmentioning
confidence: 99%